1997
DOI: 10.1093/humrep/12.10.2192
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline induces hyperactivation and acrosome reaction in spermatozoa of golden hamsters: changes in motility kinematics

Abstract: Pentoxifylline (PF) is used to enhance motility of spermatozoa from infertile human subjects. We have previously shown that 0.45 mM PF improved capacitation of spermatozoa and fertilization of oocytes in vitro in hamsters. The present study was carried out to assess PF-induced changes in motility kinematics of hamster spermatozoa by a computer-aided sperm analyser (CASA) and determine the timing of onset of hyperactivation (HA) and acrosome reaction (AR) in PF-treated spermatozoa. Motility kinematics were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Briefly, 2 µl of neat cauda epididymal content were incubated in 2 ml of pre-equilibrated TALP-PVA (Tyrode's solution supplemented with 3 mg/ml bovine serum albumin), 10 mM sodium lactate, 0.25 mM sodium pyruvate and 1 mg/ml polyvinyl alcohol) and incubated in a humidified atmosphere of 5% CO 2 in air at 37°C. The following reagents were included in the culture medium as indicated in the results: pentoxifylline [9-(5-oxohexyl)-3,7-dimethylxanthine], 0.45 mM (Rupasri et al, 1995;Jayaprakash et al, 1997); 4,4-diisothiocyanatostilbene-2,2 disulphonic acid (DIDS), 1 mM (Visconti et al, 1990); N- [2-(p-bromocinnamylamino)ethyl]5-isoquinolinesulphonamide (H89);10 µM (Leclerc et al, 1996); STP 1 nM (Lax et al, 1994); tyrphostin A-47, 0.1 mM (Leyton et al, 1992); aristolochic acid, 0.4 mM (Garde and Roldan, 1996); and progesterone, 0.1 mM (Kay et al, 1994). All test compounds were added from the start of the culture period.…”
Section: Incubation Of Spermatozoa With Pentoxyfilline Inhibitors Anmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, 2 µl of neat cauda epididymal content were incubated in 2 ml of pre-equilibrated TALP-PVA (Tyrode's solution supplemented with 3 mg/ml bovine serum albumin), 10 mM sodium lactate, 0.25 mM sodium pyruvate and 1 mg/ml polyvinyl alcohol) and incubated in a humidified atmosphere of 5% CO 2 in air at 37°C. The following reagents were included in the culture medium as indicated in the results: pentoxifylline [9-(5-oxohexyl)-3,7-dimethylxanthine], 0.45 mM (Rupasri et al, 1995;Jayaprakash et al, 1997); 4,4-diisothiocyanatostilbene-2,2 disulphonic acid (DIDS), 1 mM (Visconti et al, 1990); N- [2-(p-bromocinnamylamino)ethyl]5-isoquinolinesulphonamide (H89);10 µM (Leclerc et al, 1996); STP 1 nM (Lax et al, 1994); tyrphostin A-47, 0.1 mM (Leyton et al, 1992); aristolochic acid, 0.4 mM (Garde and Roldan, 1996); and progesterone, 0.1 mM (Kay et al, 1994). All test compounds were added from the start of the culture period.…”
Section: Incubation Of Spermatozoa With Pentoxyfilline Inhibitors Anmentioning
confidence: 99%
“…An SMI value ജ1200 indicated that the spermatozoa were capacitated. Sperm motility was determined using a standard procedure (Bavister and Andrews, 1988;Rupasri et al, 1995;Jayaprakash et al, 1997).…”
Section: Sperm Motilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Pentoxifylline, clinically used to enhance motility of sperm from infertile men, is a phosphodiesterase inhibitor leading to an increase in intracellular cAMP level [17]. In hamsters, pentoxifylline induces capacitation, hyperactivation, and acrosome reaction, and improves fertilization rates in vitro [16,18]. The application of pentoxifylline contributes to enhancement of thawed sperm motility [4] and selection of viable sperm in intracytoplasmic sperm injection [10].…”
mentioning
confidence: 99%